Optimasi Waktu Inkubasi Lactobacillus rhamnosus SKG 34 Dalam Produksi Enzim Penggumpal Susu - Setiadarma, Wulandari; Mayun Permana, Dewa Gede; Ayu Nocianitri, Komang (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i02.p01, 2020)
This study aims to determine the effect of incubation time on milk clotting enzyme (MCE) activity produced by L. rhamnosus SKG 34 and determine the optimum incubation time to produce the highest its activity. This study used a randomized block design (RBD) with incubation time as a treatment consisting of 8 levels, that were 6 hours, 12 hours, 18 hours, 24 hours, 30 hours, 36 hours, 42 hours, and 48 hours. Data were analyzed with Variance Analysis (ANOVA) than followed by Duncan Multiple Range Test (DMRT). The analyzed were repeated 3 times resulting in 24 experimental units. The results showed that the incubation time significantly affected protease activity, MCE activity, specific protease activity and ratio of MCE to protease but did not affect the total LAB. The optimum incubation time of L. rhamnosus SKG 34 is 12 hours with total LAB 1.83 x 109 CFU/ml and protease activity 180.67 U/ml, MCE activity 595.06 SU, protease spesific activity 73.149 U/mg and ratio of MCE to protease 3.29 SU/U. Keywords : incubation time, Enzyme protease, Lactobacillus rhamnosus SKG 34, Milk clotting enzyme.